Self-report measures of executive functioning are a determinant of academic performance in first-year students at a university of applied sciences - Baars, Maria A.; Nije Bijvank, Marije; Tonnaer, Geertje H.; Jolles, Jelle (Frontiers in Psychology, 2015)
Recent studies in late adolescents (age 17+) show that brain development may proceed till around the 25th year of age. This implies that study performance in higher education could be dependent upon the stage of brain maturation and neuropsychological development. Individual differences in development of neuropsychological skills may thus have a substantial influence on the outcome of the educational process. This hypothesis was evaluated in a large survey of 1760 first-year students at a University of Applied Sciences, of which 1332 are included in the current analyses. This was because of their fit within the age range we pre-set (17-20 years’ old at start of studies). Student characteristics and three behavioural ratings of executive functioning (EF) were evaluated with regard to their influence on academic performance. Self-report measures were used: self-reported attention, planning, and self-control & self-monitoring. Results showed that students with better self-reported EF at the start of the first year of their studies obtained more study credits at the end of that year than students with a lower EF self-rating. The correlation between self-control & self-monitoring on the one hand, and study progress on the other, appeared to differ for male and female students and to be influenced by the level of prior education. The results of this large-scale study could have practical relevance. The profound individual differences between students may at least partly be a consequence of their stage of development as an adolescent. Students who show lower levels of attention control, planning and self-control/self-monitoring can be expected to have a problem in study planning and study progress monitoring and hence study progress. The findings imply that interventions directed at the training of these (executive) functions should be developed and used in higher education in order to improve academic achievement, learning attitude and motivation.